Synthesis and Characterization of Fe-doped Hydroxyapatite - Kabir, S. F.; Ahmed, S.; Mustafa, A. I.; Ahsan, M.; Islam, S. (Bangladesh Journal of Scientific and Industrial Research, 2012)
Fe-doped hydroxyapatite bio-ceramic material has been successfully synthesized by wet chemical precipitation method using waste egg shell as Ca precursor and (NH4)2HPO4 as P precursor. Two different concentrations of doping solutions (0.1 M and 0.05 M) were chosen and the developed apatite was characterized by using FT-IR, XRF, XRD and SEM techniques. Observed data were in excellent agreement with the standard values for hydroxyapatite which indicated successful formation of the Fe- doped apatite of different concentrations. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10711 Bangladesh J. Sci. Ind. Res. 47(1), 1-8, 2012